Indoor tanning prevalence after the International Agency for Research on Cancer statement on carcinogenicity of artificial tanning devices: systematic review and meta‐analysis. (1st April 2020) - Rodriguez‐Acevedo, A.J.; Green, A.C.; Sinclair, C.; van Deventer, E.; Gordon, L.G.
Summary: Background: Exposure to artificial tanning devices is carcinogenic to humans, and government regulations to restrict or ban indoor tanning appear to be increasing. Objectives: We evaluated changes in the international prevalence of indoor tanning among adolescents and adults after artificial tanning devices were classified as carcinogenic by the International Agency for Research on Cancer (IARC) in 2009. Methods: Systematic searches in PubMed and Web of Science databases were undertaken. Overall, 43 studies reporting 'ever' or 'past‐year' indoor tanning exposure after 2009 were identified. We used metaregression analysis to evaluate the prevalence of indoor tanning over time. Random effects meta‐analysis was used to summarize the prevalence of indoor tanning in adolescents and adults according to sex, region and presence of age prohibitions. Results: Global prevalence of indoor tanning in adolescents for 2013–2018 was 6·5% [95% confidence interval (CI) 3·3–10·6], 70% lower than the 22·0% (95% CI 17·2–26·8) prevalence for 2007–2012. Among adults, the prevalence was 10·4% (95% CI 5·7–16·3) for 2013–2018, a decrease of 35% from 18·2% for 2007–2012. Since 2009, the overall past‐year prevalence among adolescents was 6·7% (95% CI 4·4–9·6) and 12·5% (95% CI 9·5–15·6) among adults. The prevalence of tanning indoors in the past year was similar in North America (adults, 12·5%; adolescents, 7·6%) and Europe (adults, 11·1%; adolescents, 5·1%). In 2009, three countries had regulations restricting indoor tanning, compared with 26 countries today. Conclusions: Prevalence of indoor tanning has declined substantially and significantly in adolescents and adults since the 2009 IARC statement, reflecting the rise in regulations that limit this source of unnecessary exposure to carcinogenic ultraviolet radiation. What is already known about this topic? Indoor tanning is associated with an increased risk of melanoma. A meta‐analysis of worldwide indoor tanning prevalence for 1986–2012 found a past‐year prevalence of 18% in adolescents and 14% in adults, with higher prevalences during the period 2007–2012. Policies to regulate indoor tanning began to be implemented across the globe in 2009. Only one study carried out in the U.S.A. has evaluated the efficacy of such policies in reducing indoor tanning prevalence. What does this study add? For the period 2013–2018, we found indoor tanning prevalences of 6·7% in adolescents and 11·9% in adults. This implies a reduction in indoor tanning use of 70% in adolescents and 35% in adults during the last 10 years. Our study encourages policy makers to strengthen indoor tanning regulations that reduce sunbed use among the general population in order to produce maximum public health benefit.